1923 N.D. Laws 380, ch. 266, § 6. - (:unkn) unknown (General Publisher, 1923)
Sec. 6. Carrying Pistol Concealed. No person shall carry a pistol or revolver concealed in any vehicle or in any package, satchel, grip, suit case or carry in any way or upon his person, except in his dwelling house or place of business, without a license therefor as hereinafter provided. Violations of this section shall be punished by imprisonment for not less than one year, and upon conviction the pistol or revolver shall be confiscated or destroyed.
--
Keywords: CARRY - CONCEALED